Global variation in the incidence and outcome of emergency medical services witnessed out-of-hospital cardiac arrest: A systematic review and meta-analysis. (June 2022) - Gowens, Paul; Smith, Karen; Clegg, Gareth; Williams, Brett; Nehme, Ziad
Abstract: Aim of the review: To examine global variation in the incidence and outcomes of emergency medical services (EMS) witnessed out-of-hospital cardiac arrest (OHCA). Data sources: We systematically reviewed four electronic databases for studies between 1990 and 5th April 2021 reporting EMS-witnessed OHCA populations. Studies were included if they reported sufficient data to calculate the primary outcome of survival to hospital discharge or 30-day survival. Random-effects models were used to pool incidence and survival outcomes, and meta-regression was used to examine sources of heterogeneity. Study quality was appraised using the Joanna Briggs Institute critical appraisal tools. Results: The search returned 1178 non-duplicate titles of which 66 articles comprising 133, 981 EMS-witnessed patients treated by EMS across 33 countries were included. All but one study was observational and only 12 studies (18%) were deemed to be at low risk of bias. The pooled incidence of EMS-treated cases was 4.1 per 100, 000 person-years (95% CI: 3.5, 4.7), varying almost 4-fold across continents. The pooled proportion of survivors to hospital discharge or 30-days was 20% overall (95% CI: 18%, 22%; I 2  = 98%), 43% (95% CI: 37%, 49%; I 2  = 94%) for initial shockable rhythms and 6% (95% CI: 5%, 8%; I 2  = 79%) for initial non-shockable rhythms. In the meta-regression analysis, only region and aetiology were significantly associated with survival. When compared to studies from North America, pooled survival was significantly higher in studies from Europe (14% vs. 26%; p = 0.04) and Australasia (14% vs. 31%, p < 0.001). Conclusion: We identified significant global variation in the incidence and survival outcome of EMS-witnessed OHCA. Further research is needed to understand the factors contributing to these variations.